The Endovascular Management of an Iatrogenic Superior Gluteal Artery Rupture Following Bone Marrow Biopsy - De Gregorio, Claudia (Intern Med, 2017)
We herein report an uncommon case of a life-threatening retroperitoneal hematoma after a bone marrow biopsy. Two hours after iliac crest bone harvesting, the patient experienced syncope and severe hypotension. Urgent contrast-enhanced computed tomography demonstrated extravasation from the superior gluteal artery. Transcatheter coil embolization was performed successfully, without complications. Life-threatening complications caused by retroperitoneal bleeding after bone marrow biopsy are very rare. There are few reports on the use of endovascular treatment in the management of life-threatening hemorrhagic complications after bone marrow biopsy.